Academic Senate Minutes 2004-12-16 - Academic Senate:::::::::
Chair's Report. Special Report: GE Initiative Q & A. Resolution in Support of Boycotting Holt, Rinehart and Winston and Glencoe/McGraw-Hill Publishers approved. Course Outline Policy First Reading. Posthumous Certificate of Recognition for Jessica Liparini approved. Resolution re-nominating Kathy Kaiser for Faculty Trustee approved. President report. Provost report.